Irrigation System Performance Evaluation of Sub Irrigation Area of Jejeruk Kiri Tambran Using Public Works Minister’s Regulation No. 32 in 2007 and Fuzzy Set Theory - Sahilda Swabawani; Edijatno Edijatno; Bachmid Tohary (IPTEK Journal of Proceedings Series, 2017)
Sub irrigation area of Jejeruk Kiri Tambran, physically, has performance degradation due to aging buildings and nature factors. Therefore, performance evaluation of irrigation system is needed as a part of the asset management of irrigation to determine the functioning of the irrigate ion asset. The procedures of performance evaluation refers to Public Works Minister’s Regulation No. 32 in 2007, concerning to Operation and Maintenance of Irrigation System, which is consist of 6 main aspects, there are physical infrastructure, productivity of planting, supporting facilities of operation and maintenance, personnel organization, documentation, and water user farmer association. This kind of evaluation contains fuzziness and uncertainty in valuing based on observation dan human opinion. Hence, a method that can accommodate the problem is needed, one of which is fuzzy set theory method. The aim of this research is comparing performance evaluation of irrigation system by using manual method of Bengawan Solo River Basin Agency which is refers to Public Works Minister’s Regulation No. 32 in 2007 and fuzzy set theory. The result performance value of irrigation system of sub Jejeruk Kiri Tambran is 77,69% based on manual method and 73,45% based on fuzzy method. By t-test, there is no significant diference between both methods.